Developing an integrated model for evaluating R&D organizations’ performance: combination of DEA-ANP - Hoseini, Seyed Amirali; Fallahpour, Alireza; Wong, Kuan Yew; Antuchevičienė, Jurgita (Technological and Economic Development of Economy, 2021)
Assessing the performance of the Research and development (R&D) organizations to achieve higher productivity, growth, and development is always a critical necessity. Therefore, developing a more accurate model to evaluate the performance is always required. For this purpose, this study is aimed at developing a decision-making model for evaluating R&D performance. The model comes up with determining the most proper evaluative criteria for assessing R&D organizations. Then, it integrates Data Envelopment Analysis (DEA) with Analytical Network Process (ANP) to assess R&D performance. This paper is aimed to develop an integrated model for evaluating R&D performance. The findings of the study show that the DEA-ANP model is an accurate and acceptable model for evaluating R&D organizations’ performance.